The interaction between cohesion, team trust, perceived self and collective efficacy, stress, and performance in military teams - Mikuličiūtė, Vita (Psichologija, 2012)
Even though it is usually inferred that team work is associated with positive findings (higher engagement in organizational matters, higher satisfaction with work, better performance results), this is not always true. In some occasions, team work results in poor performance outcomes because of social loafing or interpersonal conflicts. Therefore, it is important to know what psychological factors of the team determine its performance. We indicate that the main factors clearly associated with performance results are team trust, cohesion, stress, perceived self- and collective efficacy. Even though a lot of empirical studies have been made, there is still a lack of information about the interaction between these variables and the way they contribute to performance results. Besides, usually short-term artificially composed teams are under the scope of researchers. That’s why the results do not fully reflect the essence of long-term teams functioning in real-life situations. In respect to the problems mentioned above, we raised the aim of this research: to investigate the interaction between performance results and team trust, cohesion, stress, perceived collective and self-efficacy in military settings. A hypothetical model in which team trust influences cohesion and the collective efficacy acts as a mediating variable between cohesion and performance results was created. The hypothetical model has also stated that self- and collective efficacy are associated with performance results not directly, but through the perceived stress. In this research, 160 military men of professional service took part. Of them 94.4% (151) were males and 3.8% (6) females. The age of the participants ranged from 19 to 37, mean 24.6 years. The participants belonged to 28 teams (military sections) and were selected based on the information about their team functioning. Only the teams in which their members were constantly working together were included in the research. Aggregated results were used in the statistical analysis. For the purpose of the research, three questionnaires were developed: the Military Stress Questionnaire (Cronbach α = 0.92), the Questionnaire of the Perceived Military Collective Efficacy (Cronbach α = 0.93), the Questionnaire of the Perceived Military Self-efficacy (Cronbach α = 0.94). Two scales used in this research were developed by other authors: the Intrateam Trust Scale (DeJong and Elfring, 2010; Cronbach α = 0.88) and The Perceived Cohesion Scale (Bollen and Hoyle, 1990; Cronbach α = 0.85). Team performance results were based on the evaluations of the field training. The results indicate that almost all variables of our research are intercorrelated at a statistically significant level. Performance results positively correlate with the perceived self- and collective efficacy, team trust and team cohesion. No statistically significant correlation was found between stress and performance results. Besides, a high correlation between cohesion and team trust was revealed, which indicates the multicollinearity problem between these two variables. Cohesion and team trust were united, and a hypothetical model was developed using the path analysis. It shows that cohesion and team trust influences performance results not directly: the perceived collective efficacy acts as a mediating variable. Besides, self-efficacy influences the perceived collective efficacy, and the collective efficacy influences the stress level. Several important conclusions from the obtained results could be made. First, a high collective efficacy can diminish military stress and thus act as a protective factor against the formation of PTSD and other psychopathologies. Secondly, the perceived collective efficacy is the only variable that influences the performance results directly. In order to improve the results of the team, it is important to monitor and raise the levels of collective efficacy. Thirdly, cohesion and team trust have important implications not only for the perceived team capabilities, but also for the perceived one’s own capabilities.